Neuroanatomical dysmorphology of the medial superior olivary nucleus in sudden fetal and infant death - Lavezzi, Anna M. (Frontiers in Human Neuroscience, 2012)
This study expands our understanding of the organization of the human caudal pons, providing a morphologic characterization of the medial superior olivary nucleus, component of the superior olivary complex, that plays an important role in the processing of acoustic information. We examined victims of sudden unexplained fetal and infant death and controls (n=75), from 25 gestational weeks to 8 months of postnatal age, by complete autopsy and in-depth autonomic nervous system histological examination, particularly of the medial superior olivary nucleus, the focus of this study. Peculiar cytoarchitectural features of the medial superior olivary nucleus were found in sudden death cases, such as hypoplasia/agenesis and immature hypercellularity, frequently related to dysgenesis of contiguous structures involved in respiratory rhythm-generating circuit, in particular to hypoplasia of the retrotrapezoid and the facial nuclei. We propose the involvement of this nucleus in more important functions than those related to hearing, as breathing and, more extensively, all the vital activities. Besides, we highlight the fundamental role of the maternal smoking in pregnancy as etiological factor in the dysmorphic neuroanatomical development of the medial superior olivary nucleus.